Meeting of Vedanta and Transcendentalism for Global Harmony: A Study of Selected Works by Emerson, Whitman and Vivekananda - Priyanka Gupta; Vinod Solanki (Progress in Language, Literature and Education Research Vol. 7, 2024)
The term Vedanta is derived from two Sanskrit words: Veda means knowledge and Anta means end or conclusion. Thus Vedanta means the culmination of knowledge. Vedanta refers to the system of Jnana Yoga that attempts to guide an individual to enlightenment. It can be also said that Vedanta is a system of philosophy that further develops the implications in the Upanishads that all reality is a single principle, Brahman, and teaches that the believer’s goal is to transcend the limitations of the physical self and realize one’s unity with Brahman, the Absolute. Emerson and Whitman were the pivotal figures in the endowment of the Transcendental Club. Their mindset and the thought process were flooded with the tempest of the spiritual knowledge of the Oriental scriptures; and their idealistic temperament revolted against the rationalism prevailing in the 18th century America. The transcendentalism was not a mere movement but a belief which realised that the human spirit and the natural universe were the expressions of God; that all things worked together for good; that the achievement of self- reliance helps man to grow virtuous; and that all objects of nature and society develop in conformity with the moral and the Divine laws of God. The emergence of the Transcendental movement was a Divine Providence for the forthcoming Chicago Convention and Vivekananda’s message of Vedanta to the world. Vedanta speaks of unity among all beings and objects of the world with the Divine; and, seeking union of the human soul with the Divine soul; of the microcosm with the macrocosm, is its ultimate goal. Vivekananda, the universal teacher of Vedanta, preached it in its real form, relying on the essence of it and believing that every individual is a part and parcel of the Supreme Power. He made Vedanta a practical religion and preached the phenomenon of “service to man is service to God.” He sought the merger of the human being with the Divine as the most essential for spreading the message of religious harmony and universal unity. This paper is an attempt to trace the meeting points of Vedanta and Transcendentalism; to identify the role of Transcendentalism in paving the mental soil of the West for the ascension of Swami Vivekananda on the material plain of the Occidental society; and most significantly, the evolution of Practical Vedanta for the upliftment and betterment of one and all, towards the global harmony. Vedanta is understood as a state of transcendence and not as a concept that can be grasped by the intellect alone. The philosophy of Vedanta propounds the fact that every being in the universe, every spec, each and every particle, is pervaded by the Supreme Power, the glory of God is manifested in all beings and particles.